2014
DOI: 10.3390/cancers6020646
|View full text |Cite
|
Sign up to set email alerts
|

Stat3 and Gap Junctions in Normal and Lung Cancer Cells

Abstract: Gap junctions are channels linking the interiors of neighboring cells. A reduction in gap junctional intercellular communication (GJIC) correlates with high cell proliferation, while oncogene products such as Src suppress GJIC, through the Ras/Raf/Erk and other effector pathways. High Src activity was found to correlate with high levels of the Src effector, Signal Transducer and Activator of Transcription-3 (Stat3) in its tyrosine-705 phosphorylated, i.e., transcriptionally activated form, in the majority of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…It has been shown that down-regulation of GJA1 can result in aggressive growth of breast and lung cancer. [5][6][7] In contrast, forced expression of GJA1 in various tumor cells can restore normal cell phenotypes and well differentiation. 8 These findings indicated a possible role of GJA1 as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that down-regulation of GJA1 can result in aggressive growth of breast and lung cancer. [5][6][7] In contrast, forced expression of GJA1 in various tumor cells can restore normal cell phenotypes and well differentiation. 8 These findings indicated a possible role of GJA1 as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary reports suggest that GSTP1 promoter region hypermethylation suppresses expression of the gene and contributes to an increase in the incidence of cancer (Bakker et al, 2002;Zhong et al, 2002;Jain et al, 2012). Moreover, the SOCS1 gene TSG located on chromosome 16p13.13 and the JAK-binding protein encoded by this gene are both regulated by the JAK/STAT signalling pathway, which is not only correlated with the regeneration of hepatocytes but is also relevant to the oncogenesis of various types of tumours, including HCC (Clark et al, 2013;Guy et al, 2014). In addition, SOCS1 promoter region methylation is related to decreased or abnormal expression of SOCS1 in human HCC (Yoshikawa et al, 2001), suggesting that the methylation of SOCS1 may participate in the development of HCC (Saelee et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Coexistent activation of src and its effector molecule STAT3 is also observed in NSCLC cell lines. STAT3 deactivation results in a reduction in gap junctional communication exclusively in normal cells or in lines with low Src activity and high levels of gap junction communication (7). Similarly, STAT3 blockage abrogated junctional permeability in normal liver cells with high GJIC (3).…”
Section: Introductionmentioning
confidence: 98%
“…The study showed that gap junctions require the activation of STAT3 in order to maintain intracellular communication in non neoplastic and neoplastic lung cell lines. Cell proliferation is generally associated with a reduction in GJIC (7). Coexistent activation of src and its effector molecule STAT3 is also observed in NSCLC cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation